Teaching asistants in classes in full-service schools: roles, tools and responsibilities - Smuts, Suzanne; Swart, Estelle (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
Inclusive education is a global movement aimed at providing access to education and ensuring the participation and success of all learners. The implementation of such a system is complex and challenging. One of the implementation strategies used in South Africa is the utilization of full-service schools. Teaching assistants are appointed to support teachers in their classes. These staff members are employed, despite the uncertainty of whether they add value and what their roles are. Cultural historical activity theory was used as the theoretical framework for this study, which aimed to explore the roles and experiences of teaching assistants who work in resource classes in full-service schools. This study employed an interpretive case study design. Data were collected primarily through individual interviews with eight research participants selected through purposive and snowball sampling. The data were analyzed using thematic and activity systems analyses. The findings revealed that teaching assistants are perceived as valuable assets in resource classes when there are specific affordances such as personal characteristics, clear communication, cooperation, and a good relationship between teachers and teaching assistants.
Journal article published in African Perspectives of Research in Teaching & Learning APORTAL Vol. 7 (3) (2023)
Keywords: Collaboration; Cultural-historical activity theory; Full-service schools; Inclusive education; Resource classes; Teaching assistant; Teachers' assistants; Inclusive education -- South Africa